Nutrient Expert Improves Nitrogen Efficiency and Environmental Benefits for Summer Maize in China. (1st May 2017) - Zhang, J. J.; He, P.; Xu, X. P.; Wang, Y. L.; Jia, L. L.; Cui, R. Z.; Wang, H. T.; Zhao, S. C.; Ullah, S.
Abstract : Core Ideas: Nutrient expert is a nutrient decision support tool and this study confirmed that it could be used in north‐central China. The continual performance of nutrient expert was evaluated through multiple‐point field experiments. This is the first report of nutrient expert on improving environmental benefits of summer maize. Modern agriculture needs environmentally friendly approaches to increase production, improve nitrogen use efficiency (NUE), and promote ecologically sustainable agriculture. This study was conducted from 2010 to 2014 in 389 farmers' fields across major summer maize growing regions in north‐central China to evaluate the continual performance of the nutrient expert (NE) system for improving NUE and environmental benefits. Results indicated that NE significantly increased grain yield and profitability by reducing N fertilizer rate by 35.1% (84.6 kg N ha −1 ), increasing the K rate by 68.1% (25.8 kg K2 O ha −1 ), and keeping the P rate the same as the farmers' practice (FP). On average, NUE achieved in the NE treatment was significantly higher than for FP and fertilizer recommendation based on soil testing (OPTS). The NE increased agronomic efficiency of nitrogen (AEN) by 50.8 and 17.3%, recovery efficiency of nitrogen (REN) by 67.7 and 15.9%, and partial factor productivity of nitrogen (PFPN) by 43.8 and 21.2% compared with FP and OPTS, respectively. Furthermore, the calculated total N2 O emission, total greenhouse gas (GHG) emission, and GHG emission intensity were 35.1 and 17.5%, 35.2 and 18.4%, and 37.3 and 17.4% lower in the NE treatment when compared with FP and OPTS, respectively. The differences in yield, economic benefits, NUE, and GHG emission among NE, FP, and OPTS treatments confirmed that NE is a promising nutrient decision support tool and has the potential to improve NUE and environmental benefits for summer maize ( Zea mays L.) in north‐central China.